Reader Response: Race-Ethnic Disparities in Rates of Declination of Thrombolysis for Stroke. (13th December 2022) - Patel, Karan; Wolfe, Jared; Siegler, James E.
Abstract : We applaud Mendelson et al. 1 for their investigation showing racial differences among those who decline treatment with thrombolytics.